Reagent selection for recovery of nickel and cobalt from nitric acid nickel laterite leach solutions by solvent extraction - Hutton-Ashkenny, M.; Ibana, Don; Barnard, K. (Elsevier, 2015)
© 2015 Elsevier Ltd. All rights reserved.There is currently no commercial process for recovery of nickel and cobalt from a nitrate-based laterite leach liquor via solvent extraction. Such a process is becoming of interest as nitric acid leaching of nickel laterite ores is progressed by Direct Nickel. Although commercially proven solvent extraction processes do exist for nickel and cobalt extraction from sulphate-based laterite leach liquors, little is known regarding their application to nitrate-based liquors. In the present paper three different solvent extraction systems are compared from a commercialisation standpoint in order to inform future process development. These systems were: neodecanoic acid (Versatic™10)/tributylphosphate (TBP), Versatic 10/pyridine carboxylate (PC), and an aliphatic hydroxyoxime based extractant (LIX®63)/Versatic 10/PC. On the basis of acceptable separation of nickel and cobalt from manganese and magnesium, and ease of metal stripping, the synergistic combination of Versatic 10 and a pyridine carboxylate (in this case nonyl-4-PC) was identified as the most promising system for application to a nitrate-based laterite leach liquor.